2017
DOI: 10.3390/w9120945
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Hydraulic Jump in a Gradually Expanding Rectangular Stilling Basin with Roughened Bed

Abstract: Abstract:The paper presents the results of an experimental study carried out to investigate the effect of geometric and hydraulic parameters on energy dissipation and location of the hydraulic jump, with a change in the height of roughness elements and the divergence of walls in different discharges. Experiments were conducted in a horizontal rectangular basin with gradual expansion 0.5 m wide and 10 m long. Four physical models were fixed in the flume. The measured characteristics of the hydraulic jump with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…The Figure 17 indicates that the results obtained by the Equation 31show ± 26% variation with the corresponding observed data. Additionally, the difference between the computed data of L r /y 1 by Equation (32) and the experimental data of present research, Ead and Rajaratnam [15] and Carollo et al [17] are in the range of ±30% and only 9 out of the 356 L r /y 1 ratios fall beyond the mentioned error band. The following regression-based equation is defined between the estimated values, the expansion ratio and the relative roughness height.…”
Section: Methodscontrasting
confidence: 59%
See 3 more Smart Citations
“…The Figure 17 indicates that the results obtained by the Equation 31show ± 26% variation with the corresponding observed data. Additionally, the difference between the computed data of L r /y 1 by Equation (32) and the experimental data of present research, Ead and Rajaratnam [15] and Carollo et al [17] are in the range of ±30% and only 9 out of the 356 L r /y 1 ratios fall beyond the mentioned error band. The following regression-based equation is defined between the estimated values, the expansion ratio and the relative roughness height.…”
Section: Methodscontrasting
confidence: 59%
“…The experimental values of L r /y 1 in the present research, Carollo et al [17] and Ead and Rajaratnam [15] are compared with the values computed by Equations (31) and (32) in the Figure 17a,b, respectively. The Figure 17 indicates that the results obtained by the Equation 31show ± 26% variation with the corresponding observed data.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Carollo and Ferro [21] studied the characteristics of hydraulic jump on a rip-raped bed and concluded that relative sequent depth y 2 /y 1 decreases with the size of bed roughness. Hassanpour et al [22] investigated the effect of geometric and hydraulic parameters on energy dissipation and location of the hydraulic jump, in different roughness heights and the divergence of walls. Their results showed that the tail-water depth, the roller length, and the hydraulic jump length on a gradual expansion basin with the rough bed were significantly smaller than that of the classical hydraulic jumps in a rectangular basin with smooth and rough bed.…”
Section: Introductionmentioning
confidence: 99%